Building Joint Programs and Support Programs in 1862 and 1890 Schools - R. E. Jones (Journal of Applied Communications, 1972)
More than 50,000 black students (1 out of every 9 black collegians in the United States) attend the unique group of institutions of higher learning—the black land-grant colleges.